Pengaruh Penambahan Iron Slag Sebagai Subtitusi Agregat Kasar Terhadap Kuat Tekan Pada Beton - Muh. Hajir Ahmad; Adnan Adnan; Hamka Hamka (Pusat Riset dan Inovasi Nasional, 2024)
Slag is the residual product of blast furnace combustion, which is produced in the form of iron slag which is still not used properly, causing problems for the environment. In line with the spirit of environmental preservation, companies producing slag waste are looking for solutions to utilize this slag waste. The aim of this research is to determine the compressive strength of iron slag waste as a partial substitute for coarse aggregate on the compressive strength of concrete and the effect of variations in the percentage of iron slag waste on the compressive strength of concrete. The data analysis technique used in this research uses descriptive parametric analysis. Data on concrete compressive strength test results is obtained from the division between the maximum load of the test object and the cross-sectional area of ​​the test object, then the data will be presented in the form of tables or graphs. The results of the research show that the influence of variations in the results of concrete compressive strength testing which takes into account variations in the mixture of iron slag waste with 3 variations, namely 0% (normal concrete), 5% and 10% of some of the coarse aggregate, results in concrete testing at the age of 28 days. in normal concrete or variations of 0% Iron slag waste with an average of 21.89 MPa. For a variation of 5% iron slag waste with an average of 23.12 Mpa. And for variations of 10% iron slag waste with an average of 26.04 MPa. From the results of adding or replacing coarse aggregate using iron slag waste in the mixture, the compressive strength of the concrete has increased, as is the result obtained, namely from adding 5% iron slag waste, an increase of 1.23 MPa compared to normal concrete. and the addition of iron slag waste by 10% decreased by 4.15 MPa from normal concrete.